Triple Conductive Wiring by Electron Doping, Chelation Coating and Electrochemical Conversion in Fluffy Nb2O5 Anodes for Fast‐Charging Li‐Ion Batteries. Issue 25 (7th July 2022) - Zheng, Yongjian; Qiu, Wujie; Wang, Lei; Liu, Jianjun; Chen, Shuangqiang; Li, Chilin
Abstract: High‐rate anode material is the kernel of developing fast‐charging lithium ion batteries (LIBs). T–Nb2 O5, well‐known for its "room and pillar" structure and bulk pseudocapacitive effect, is expected to enable the fast lithium (de)intercalation. But this property is still limited by the low electronic conductivity or insufficient wiring manner. Herein, a strategy of triple conductive wiring through electron doping, chelation coating, and electrochemical conversion inside the microsized porous spheres consisting of dendrite‐like T–Nb2 O5 primary particles is proposed to achieve the fast‐charging and durable anodes for LIBs. The penetrative implanting of conformal carbon coating (derivative from polydopamine chelate) and NbO domains (induced by excess discharging) reinforces the global supply of electronically conductive wires, apart from those from Co/Mn heteroatom or O vacancy doping. The polydopamine etching on T–Nb2 O5 spheres promotes their evolution into fluffy morphology with better electrolyte infiltration. The synergic electron and ion wiring at different scales endow the modified T–Nb2 O5 anode with ultralong cycling life (143 mAh g −1 at 1 A g −1 after 8500 cycles) and high‐rate performance (144.1 mAh g −1 at 10.0 A g −1 ). The permeation of multiple electron wires also enables a high mass loading of T–Nb2 O5 (4.5 mg cm −2 ) with a high areal capacity of 0.668 mAh cm −2 even after 150 cycles. Abstract : A strategy of triple conductive wiring through electron doping, chelation coating, and electrochemical conversion inside the microsized porous spheres consisting of dendrite‐like T–Nb2 O5 primary particles is proposed to achieve the fast‐charging and durable anodes. The synergic electron and ion wiring at different scales endows the modified T–Nb2 O5 anode with ultralong cycling life and high‐rate performance.